Fibrosis modeling choice affects morphology of ventricular arrhythmia in non-ischemic cardiomyopathy - Myklebust, Lena; Maleckar, Mary M.; Arevalo, Hermenegild (Frontiers in Physiology, 2024)
Patients with non-ischemic cardiomyopathy (NICM) are at risk for ventricular arrhythmias, but diagnosis and treatment planning remain a serious clinical challenge. Although computational modeling has provided valuable insight into arrhythmic mechanisms, the optimal method for simulating reentry in NICM patients with structural disease is unknown. Here, we compare the effects of fibrotic representation on both reentry initiation and reentry morphology in patientspecific cardiac models. We investigate models with heterogeneous networks of non-conducting structures (cleft models) and models where fibrosis is represented as a dense core with a surrounding border zone (non-cleft models). Using segmented late gadolinium enhanced (LGE) cardiac magnetic resonance of five NICM patients, we created 185 3D ventricular electrophysiological models with different fibrotic representations (clefts, reduced conductivity and ionic remodeling). Reentry was induced by electrical pacing in 647 out of 3145 simulations.Both cleft and non-cleft models can give rise to double-loop reentries meandering through fibrotic regions (Type 1-reentry). When accounting for fibrotic volume, the initiation sites of these reentries are associated with high local fibrotic density (mean LGE in cleft models: p< 0.001, core volume in non-cleft models: p = 0.018, negative binomial regression). In non-cleft models, Type 1-reentries required slow conduction in core tissue (non-clefts c models) as opposed to total conduction block.Incorporating ionic remodeling in fibrotic regions can give rise to single-or double-loop rotors close to healthy-fibrotic interfaces (Type 2-reentry). Increasing the cleft density or core-to-border zone ratio in cleft and non-cleft c models, respectively, leads to increased inducibility and a change in reentry morphology from Type 2 to Type 1. By demonstrating how fibrotic representation affects reentry morphology and location, our findings can aid model selection for simulating arrhythmogenesis in NICM.